Preliminary comparison of the direct aerosol radiative forcing over Ukraine and Antarctic AERONET sites - G. Milinevsky; Yu. Yukhymchuk; A. Grytsai; V. Danylevsky; Yu. Wang; V. Choliy (Ukrainian Antarctic Journal, 2019)
Objectives. To analyze data on aerosol optical thickness (AOT) in the atmosphere over some Ukraine and Antarctic AERONET (AErosol RObotic NETwork) sites. To determine and compare direct aerosol radiative forcing (DRF) typical values using the data from midlatitude and Antarctic AERONET sites. Methods. Retrieval and visualization of the AERONET aerosol optical thickness and radiative forcing, data analysis and interpretation of the data. Radiative forcing evaluation using Global Atmospheric ModEl (GAME) and the AERONET operational product. Results. Aerosol optical thickness measurements are considered using observations by sun/sky photometers that are part of the AERONET sites in Ukraine (Kyiv) and at two additional sites in Antarctica (Vechernaya Hill and ARM_McMurdo sites). According to the 2015–2018 measurements at the Vechernaya Hill and ARM_McMurdo sites, the AOT values are small and are in the range of 0.05–0.1 at the 340 nm wavelength. In contrast, the corresponding AOT values from Kyiv observational site are reached 0.3–0.5 and sometimes higher. Using these AOT values from Kyiv site and the urban aerosol types, the aerosol direct radiative forcing has been evaluated by the GAME code. The top of atmosphere (TOA) DRF assessment using GAME suggests the instantaneous values of –5.7 W m–2 over vegetation surface for AOT equal 0.1. Conclusions. The AERONET derived aerosol optical thicknesses over Kyiv site show the mean value of 0.3 at 340 nm; the values over two Antarctic sites are in range of 0.03 to 0.06. Calculations using a numerical code (GAME) suggested the associated TOA instantaneous DRF of –6 W m–2 to –14 W m–2 over the Kyiv site. The values calculated as part of the AERONET Kyiv site operational product are about –20 W m–2 (BOA) and about –10 W m–2 (TOA) during 2018.